DEFENSIVE PERFORMANCE INDICATORS OF THE GREEK YOUTH NATIONAL HANDBALL TEAM - Athanasios YIANNAKOS (Cluj University Press, 2016)
The aim of the present study was to assess defensive tactics among players of the Greek National Youth Team, during the 18thWorld Championship that took place in Thessaloniki. Methods: We examined the prevalence of different tactical defensive formations, their efficacy against goal-attempt shots, their outcome, as well as the goalkeeper's ability to fend-off. All games of the Greek National team were recorded and analysed with Sport scout video-analysis software for PC. The statistical analyses were performed with the SPSS 19 statistical software and the use of non-parametric Chi-square tests. Significance was set at p<0.05. Results: Data analysis revealed that the majority of the offensive attacks performed against the Greek National Team included goal-attempt shots (65.2%), whereas attacks free of goal-attempts involved only 34.8% of the recorded phases. The most prevalent tactical defensive formation applied was the 6:0 (82.1%). Among the recorded phases, defence with a fewer number of defenders was applied in 7.6%, 5:1 defence system was adopted in 4.7% and 5+1 was used on 3.2% of the phases. Goalkeepers were successful in fending-off 24.4% of the organized attacks. Conclusion: The use of the 6:0 defence formation is quite common, either in a more offensive manner or with adaptations. It is highly likely that the frequent use of this formation in a passive manner and the application of defence with fewer defenders resulted in a relatively low ranking of the Greek team.